Understanding contrasting municipal standpoints on mining investments in relation to framings of mining and rural development : a comparative case study of Karlsborg and Jokkmokk municipalities in Sweden - Sörman Laurien, Elvira (SLU/Dept. of Urban and Rural Development, 2019)
Overs the last couple of years, Sweden has seen an increasing trend in mining investments. New to this trend is that also places in southern Sweden are involved; places that may not historically be familiar with mining. Many of the places that face potential mines are rural places with different challenges and opportunities in relation to their rurality. In Sweden, the municipality is the governmental body closest to the citizens and is responsible for many welfare related services. At the same time, the municipalities are also excluded from certain decision making process that affect them, e.g. due to Swedish mining laws. This thesis explores contrasting standpoints on mining investments by Swedish municipalities in relation to framings of rural development, by probing the two cases of Jokkmokk municipality in northern Sweden and Karlsborg municipality in southern Sweden, who have taken contrasting official municipal standpoints on potential mining investments in their respective municipalities. An analytical framework is formulated which highlights linkages between understandings of mining and rural development and the standpoints that are taken. Results indicate that negative standpoints are connected to an economy, population and employment related framing of mining and rural development, and positive standpoints to a place or community related framing, and that governance is an important layer in the understanding of the standpoints. Furthermore, this thesis highlights the importance of including the Swedish municipality in research on processes of natural resource extraction and rural development.